Hubungan Teori Belajar Sibernetik dengan Efektivitas Pembelajaran Aqidah Akhlaq - Rahmansyah Rahmansyah; Muhammad Aidil_Nur; Muhammad Khalidin (Transformasi Manageria: Journal of Islamic Education Management, 2021)
Cybernetic learning theory which has an average result of 51.75, median of 49, mode of 46.8, variance of 30.19 and standard deviation of 5.49, can be accepted with a significant tolerance limit. This indicates a positive and significant relationship. The effectiveness of learning aqidah morals of students at MTs IKABA Gebang has an average result of 52.7, median of 53.6, mode of 53, variance of 17.85 and standard deviation of 4.22 acceptable with a positive and significant tolerance limit. There is a positive relationship and significant on cybernetic learning theory with the effectiveness of students' aqidah morals learning at MTs IKABA Gebang with a regression line Y= 22.37 +0.61 X. There is a significant correlation between cybernetic learning theory and the effectiveness of students learning aqidah morals at MTs IKABA Gebang after the regression test with the product moment formula with a calculated result of 0.833 with a strong or high level of relationship. From the results of the research conducted by the researchers, it is known that cybernetic learning theory is well applied and able to contribute to the effectiveness of students' moral aqidah learning at MTs IKABA Gebang, for that it is hoped that teachers will be able to apply cybernetic learning theory well so that the impact on students can have a more positive effect